Changes in antioxidant and antiinflammatory activity of black bean (Phaseolus vulgaris L.) protein isolates due to germination and enzymatic digestion. (15th July 2016) - López-Barrios, Lidia; Antunes-Ricardo, Marilena; Gutiérrez-Uribe, Janet A.
Highlights: Germination improved the antiinflammatory activity of protein hydrolysates. Simulated gastrointestinal digestion increased the ORAC of protein hydrolysates. Cellular antioxidant capacity was similar for raw and most germinated hydrolysates. Abstract: Germination is an inexpensive process to improve the nutritional properties of legumes. The effect of germinating black bean seeds on the production of cotyledon protein hydrolysates (CPH) with antioxidant and antiinflammatory activities was analyzed in this research. After simulated enzymatic digestion, the oxygen radical absorbance capacity (ORAC) of CPH obtained from germinated black beans was lower than that observed for raw cotyledons. There were no significant differences among CPH cellular antioxidant activities (CAA), except for the high CAA of the 120 min hydrolysate obtained from one day germinated black bean cotyledons. The most significant changes due to germination and enzymatic hydrolysis were observed for the inhibition of nitric oxide (NO) production in macrophages. The NO synthesis inhibition observed for raw CPH was reduced after simulated gastrointestinal digestion but for germinated samples the inhibition was doubled. Peptides derived from cell wall proteins produced during germination could be responsible of antiinflammatory activity.